2021
DOI: 10.3390/s21010262
|View full text |Cite
|
Sign up to set email alerts
|

Stamping Monitoring by Using an Adaptive 1D Convolutional Neural Network

Abstract: Stamping is one of the most widely used processes in the sheet metalworking industry. Because of the increasing demand for a faster process, ensuring that the stamping process is conducted without compromising quality is crucial. The tool used in the stamping process is crucial to the efficiency of the process; therefore, effective monitoring of the tool health condition is essential for detecting stamping defects. In this study, vibration measurement was used to monitor the stamping process and tool health. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Huang and Dzulfikri transformed acceleration signals into the frequency domain and used the entire power density spectrum as input for a one dimensional CNN. They demonstrated that they can distinguish seven different wear states with more than 99% accuracy [39]. Unterberg et al recorded magnetic barkhausen noise from different material coils, created recurrence plots of the time series and used them as inputs for a two dimensional CNN.…”
Section: Deep Learning Approachesmentioning
confidence: 99%
“…Huang and Dzulfikri transformed acceleration signals into the frequency domain and used the entire power density spectrum as input for a one dimensional CNN. They demonstrated that they can distinguish seven different wear states with more than 99% accuracy [39]. Unterberg et al recorded magnetic barkhausen noise from different material coils, created recurrence plots of the time series and used them as inputs for a two dimensional CNN.…”
Section: Deep Learning Approachesmentioning
confidence: 99%
“…The data set used in the current study was extensively used in our previous study [29]. It contains progressive stamping die vibration signals acquired using an accelerometer with a sampling rate of 25.6 kHz and an axis parallel to the stroke direction of the stamping machine.…”
Section: Datasetmentioning
confidence: 99%
“…CNNs, which employ neural nodes as a type of filter, enable deep learning structures to extract features from complex and highly nonlinear signals. In our previous work [29], a CNN was used to evaluate the condition of a stamping tool, achieving favorable results; however, several problems remain to be resolved. First, to add a new class, the model must be retrained, which requires a high computational cost.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed method has less energy consumption which is suitable to be integrated in embedded system. Therefore, the methodology has been investigated in bearing, motor running noise and stamping quality monitoring areas (Wang et al , 2020; Huang and Dzulfikri, 2021; Ince, 2019; Zhang et al , 2017). Furthermore, residual learning Der-1DCNN model was studied.…”
Section: Introductionmentioning
confidence: 99%